DNA methylation and allergic sensitizations: A genome‐scale longitudinal study during adolescence. Issue 6 (5th March 2019) - Zhang, Hongmei; Kaushal, Akhilesh; Merid, Simon Kebede; Melén, Erik; Pershagen, Göran; Rezwan, Faisal I.; Han, Luhang; Ewart, Susan; Arshad, S. Hasan; Karmaus, Wilfried; Holloway, John W.
Abstract: Background: The presence of allergic sensitization has a major influence on the development and course of common childhood conditions such as asthma and rhinitis. The etiology of allergic sensitization is poorly understood, and its underlying biological mechanisms are not well established. Several studies showed that DNA methylation (DNAm) at some CpGs is associated with allergic sensitization. However, no studies have focused on the critical adolescence period. Methods: We assessed the association of pre‐ and postadolescence genome‐wide DNAm with allergic sensitization against indoor, outdoor and food allergens, using linear mixed models. We hypothesized that DNAm is associated with sensitization in general, and with poly‐sensitization status, and these associations are age‐ and gender‐specific. We tested these hypotheses in the IoW cohort (n = 376) and examined the findings in the BAMSE cohort (n = 267). Results: Via linear mixed models, we identified 35 CpGs in IoW associated with allergic sensitization (at false discovery rate of 0.05), of which 33 were available in BAMSE and replicated with respect to the direction of associations with allergic sensitization. At the 35 CpGs except for cg19210306 on C13orf27, a reduction in methylation among atopic subjects was observed, most notably for cg21220721 and cg11699125 ( ACOT7 ). DNAm at cg10159529 was strongly correlated with expression of IL5RA in peripheral blood ( P ‐value = 6.76 × 10 −20 ). Three CpGs (cg14121142, cg23842695, and cg26496795) were identified in IoW with age‐specific association between DNAm and allergic sensitization. Conclusion: In adolescence, the status of allergic sensitization was associated with DNAm differentiation and at some CpGs the association is likely to be age‐specific. Abstract : DNA methylation is associated with allergic sensitizations, findings from a genome‐scale longitudinal study during adolescence.